2021
DOI: 10.1021/acscatal.1c03641
|View full text |Cite
|
Sign up to set email alerts
|

Propane Dehydrogenation and Cracking over Zn/H-MFI Prepared by Solid-State Ion Exchange of ZnCl2

Abstract: Light alkanes in shale gas are an attractive source of carbon for the production of alkenes and aromatics compared to petroleum-derived naphtha. Zinc-exchanged zeolite H-MFI (Zn/ H-MFI) is active and selective for light alkane dehydrogenation and dehydroaromatization. In this study, Zn/H-MFI with varying Zn/Al ratios was prepared via solid-state ion exchange (SSIE) of ZnCl 2 and characterized by various methods. As-prepared Zn/H-MFI with Zn/Al ≤ 0.52 contains isolated [ZnCl] + and [ZnCl-(HCl)] + species; Zn/H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 84 publications
4
41
0
Order By: Relevance
“…Comparing Al/Zn and Zn 2 /Al catalysts, the pre-exponential factor increases, which can simply be explained by the previously discussed increased number of active sites present in Zn 2 /Al. From the Arrhenius plots slopes, an apparent activation energy of 145 ± 1 kJ mol –1 for all zinc-containing catalysts was calculated, which falls in the expected range from the literature (121–159 kJ mol –1 ). , …”
Section: Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Comparing Al/Zn and Zn 2 /Al catalysts, the pre-exponential factor increases, which can simply be explained by the previously discussed increased number of active sites present in Zn 2 /Al. From the Arrhenius plots slopes, an apparent activation energy of 145 ± 1 kJ mol –1 for all zinc-containing catalysts was calculated, which falls in the expected range from the literature (121–159 kJ mol –1 ). , …”
Section: Results and Discussionsupporting
confidence: 59%
“…From the Arrhenius plots slopes, an apparent activation energy of 145 ± 1 kJ mol −1 for all zinc-containing catalysts was calculated, which falls in the expected range from the literature (121−159 kJ mol −1 ). 73,74 The increased Zn mobility might also favor the displacement of the zinc atom off of the silica surface, leading to irreversible deactivation. Therefore, placing an aluminum next to a zinc atom and adding an anchor on the other side could limit displacement and increase stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The erosion of [ZnH] + species upon D 2 treatment is related to the decreased PDH activity under C 3 H 8 –D 2 reactant, further revealing the unique role of [ZnH] + species for propane activation. Indeed, the [ZnH] + species were widely reported in aluminosilicate zeolites, but their activity for alkane activation is debated. The present work not only reveals that the [ZnH] + could be stabilized by silicalite zeolites but also highlights its unique role in propane activation. More importantly, it is found that the [ZnH] + formation could be regulated by the amount of [ZnOH] + in as-prepared catalysts for improving PDH performance.…”
Section: Resultsmentioning
confidence: 61%
“…However, the cost and fast deactivation of Pt and the environmental impact associated with Cr have stimulated the exploration of alternative catalysts . Ga-, V-, Zr-, Zn-, Co-, and Fe-based materials and nanocarbon catalysts, , among others, have been investigated for this purpose. In particular, oxide supports (silica or zeolites) containing single metal sites (Ga + , Zn 2+ , Co 2+ , Fe 2+ , etc.)…”
Section: Introductionmentioning
confidence: 99%